Media optimization of antimicrobial activity production and beta-glucan content of endophytic fungi Xylaria sp. BCC 1067 - L. A. Channa Bhathiya Jayasekara; Attaporn Poonsawad; Kwanrutai Watchaputi; Songsak Wattanachaisaereekul; Nitnipa Soontorngun (Biotechnology Reports, 2022)
This simple strategy of culture media optimization allows for investigation of novel and rich source of health-promoting substances for effective microbial utilization.
Keywords: Fungal Biology and Applications; Microbial Natural Products and Biosynthesis; Chemical synthesis and alkaloids